Analysis Competency, Employee Resilience, and Leadership Impact on Organization Performance the Freight Forwarding Company - Doni Putra Utama (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to see the relationship between variables and analyze the factors that cause a decrease in organizational performance. This research uses a literature review study to systematically review previous articles to see the correlation with the current research, the results are there is a relationship between all independent variables on the dependent variable. This finding can really be a novelty in qualitative research, organizational performance can increase with competency, employee resilience, and leadership at a company's international freight forwarding. In previous research, there are many other independent variables that can improve organizational performance but they are not mentioned in this study. Within a limited time frame, the researchers determined which independent variable was most dominant.